The antecedent factors of ambiguity role and workers’ welfare in Semarang City: role theory approach - Ari Pradhanawati; Ricky Santoso Muharam; Mustofa Agung Sardjono; Chusnu Syarifa Diah Kusuma; Elia Ardyan (Cogent Social Sciences, 2024)
Indonesian women still live with negative stereotypes, which leads to limited employment opportunities for women. Women who work as laborers generally experience role conflict. Most company leaders do not understand the conditions of female workers. They demand female workers to always focus on work, which makes female workers not have a work-family balance, which means they are not experiencing a balance between family and work. This study examined the influence of dual roles and family commitment on role ambiguity and worker well-being. This research is explanatory. The sample was obtained using convenience sampling when the respondents, in this case, were female workers who attended the International Labor Day commemoration in Semarang City. The data collection technique used was a questionnaire and data analysis using SEM-PLS (Structural Equation Modeling Partial Least Square), the sample taken from 374 respondents from female workers in Semarang City. This study found that family role has a positive and significant effect on role ambiguity (β = 0.341; p < 0.001), family commitment has a significant negative impact on role ambiadverse= −0.131; p < 0.001), role ambiguity has a significant negative effect on female workers’ welfare (β= −adverse = 0.003), the role of the family has a significant adverse impact on the welfare of female workers (β= -0.175; p < 0.001), and family commitment has a significant positive effect on the welfare of women labor. Role ambiguity, characterized by uncertainty in job expectations, emerges as a critical concern. The findings show that role ambiguity significantly negatively affects workers’ welfare.